(3af HjY GdYbGQGJ (B/s - (3cjfOj, OGfjjds ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B, s, 2006)
(3jVe CgejI bhI GdEOGQI, GdehGRfI Hjf GdMjGI GdYedjI hGdTNUjI, GdESJKeGQ aj eLGd GdYbGQGJ, GdEOGQI GdbjGOjI GdMcjeI aj GdTQcGJ GdYbGQjI, THcGJ GdJShjb hcjajI HfGA SeYI WHjI, cjajI GdJZdH Ydi GdefGaSI, CSGdjH JQhjLjI SQjYI dRjGOI GdONd, GdNWI GdeKGdjI dLPH GdeTJQj, GJeGe UabGJ hRjGOI GdONd, cjajI GKHGJ bOQGJ GdSeSGQ GdegfjIs
Keywords: (3GdHGYI haf GdHjYs; (3GdYbGQGJs